2011
DOI: 10.1002/anie.201104390
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Reductive Allylation of Alkyl Halides with Allylic Acetates or Carbonates

Abstract: Transition-metal-catalyzed allylic alkylations, using a broad range of metal complexes, have been intensively studied because of their potential applications in the synthesis of new olefinic compounds in particular for total synthesis.[1] Soft nucleophiles are usually used in Pd-, [1] Mo-, [2] Ir-, [3] Ru-, [4] Rh-, [5] Pt-, [6] and even Fe-catalyzed [7] allylic substitutions. Ni, [8] Co, [9] and Cu [10] catalysts allow the use of hard nucleophiles such as alkylzinc or Grignard reagents, but limited function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(59 citation statements)
references
References 45 publications
3
56
0
Order By: Relevance
“…We identified that a combination of CoBr 2 /Mn/pyridine in CH 3 CN, as previously reported for the allyl-alkyl cross-coupling reaction, [13] afforded the desired coupling product in 84% yield (Table 1, entry 1). Without pyridine, the reduction product was rapidly the main product (Table 1, entry 2).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…We identified that a combination of CoBr 2 /Mn/pyridine in CH 3 CN, as previously reported for the allyl-alkyl cross-coupling reaction, [13] afforded the desired coupling product in 84% yield (Table 1, entry 1). Without pyridine, the reduction product was rapidly the main product (Table 1, entry 2).…”
supporting
confidence: 66%
“…Alkyl bromides bearing electron-donating groups and electron-withdrawing groups, such as ester ( Table 2, entry 9), ketal (Table 2, entry 13) efficiently reacted. Interestingly, whereas isoindole-1,3-dione and ketone groups were not tolerated in the cobalt-catalyzed allyl-alkyl cross-coupling reactions, [13] they provided moderate to good yields in this homocoupling reaction (Table 2, entries 10 and 16). Benzyl chloride, which is more reactive, could also be used in this reaction (Table 2, entryies 14 and 15).…”
mentioning
confidence: 99%
“…20 All reactions were performed under a nitrogen atmosphere unless otherwise specified. NMR spectra were recorded on JEOL α400, JNM-ECX 400 ( 1 H/400 MHz, 13 C/100 MHz), and Bulker VSP 500 ( 1 H/500 MHz, 13 The medium pressure liquid chromatography (MPLC) purifications were performed on a YAMAZEN YFLC-AI-580. Where necessary, solvents were distilled from appropriate drying agents prior to use.…”
Section: Discussionmentioning
confidence: 99%
“…The residue was purified by silica-gel column chromatography to afford (+)-WIN 64821 (6) (33.2 mg, 0.050 mmol, 59%). The NMR spectra were identical to the 13 …”
Section: Meso-folicanthine (Meso-4)mentioning
confidence: 99%
“…While most transformations based on activated alkyl electrophiles emphasize C(sp 3 )-C(sp 2 ) bond forming methods (see Sects. 2.2-2.5), the cross-coupling of allylic acetates (or carbonates) with unactivated alkyl halides represents the only example for the construction of hetero C(sp 3 )-C(sp 3 ) bonds utilizing activated alkyl electrophiles [36][37][38].…”
Section: Coupling With Activated Alkyl Electrophilesmentioning
confidence: 99%